Therapeutic development and use before and during the Ebola outbreak. (May 2015) - Zeitlin, Larry
Biography: Larry Zeitlin speaks to Emily Hargrave, Commissioning Editor: Larry received a BA in Biophysics and his doctorate in Reproductive Biology from The Johns Hopkins University. After serving as a Research Scientist at ReProtect, LLC (MD, USA), and a Senior Scientist at Epicyte Pharmaceutical (CA, USA), together with Dr Kevin Whaley, he cofounded Mapp Biopharmaceutical and LeafBio, Inc. CA, USA). He has been an adjunct faculty member of the Biodesign Institute at Arizona State University since 2004. Larry's career focus has been on the development of monoclonal antibody-based products to address unmet public health needs.